The Chinese herbal medicine Dai-Zong-Fang promotes browning of white adipocytes in vivo and in vitro by activating PKA pathway to ameliorate obesity - Xu, Jing; Zhang, Li-Wei; Feng, Hui; Tang, Yang; Fu, Shou-Qiang; Liu, Xi-Ming; Zhu, Xiao-Yun (Frontiers in Pharmacology, 2023)
Introduction: The global prevalence of obesity is rising rapidly. Conversion of white adipose tissue (WAT) into beige adipose tissue with heat-consuming characteristics, i.e., WAT browning, effectively inhibits obesity. Dai-Zong-Fang (DZF), a traditional Chinese medicine formula, has long been used to treat metabolic syndrome and obesity. This study aimed to explore the pharmacological mechanism of DZF against obesity. Methods:In vivo, C57BL/6J mice were fed high-fat diets to establish the diet-induced obese (DIO) model. DZF (0.40 g/kg and 0.20 g/kg) and metformin (0.15 g/kg, positive control drug) were used as intervention drugs for six weeks, respectively. The effects of DZF on body size, blood glucose and lipid level, structure and morphology of adipocytes and browning of inguinal WAT (iWAT) in DIO mice were observed. In vitro, mature 3T3-L1 adipocytes were used as the model. Concentrations of DZF (0.8 mg/mL and 0.4 mg/mL) were selected according to the Cell Counting Kit-8 (CCK8). After 2d intervention, lipid droplet morphology was observed by BODIPY493/503 staining, and mitochondria number was observed by mito-tracker Green staining. H-89 dihydrochloride, a PKA inhibitor, was used to observe the change in browning markers′ expression. The expression levels of browning markers UCP1 and PGC-1α and key molecules of PKA pathway were detected in vivo and in vitro. Results:In vivo, compared with vehicle control group, 0.40 g/kg DZF significantly reduced obesity in DIO mice from body weight, abdomen circumference, Lee′s index, and WAT/body weight (p < 0.01 or p < 0.001). 0.40 g/kg DZF also significantly reduced fasting blood glucose (FBG), serum triglycerides (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) (p < 0.01 or p < 0.001). The iWAT′s morphology and mitochondria were browning after DZF intervention. In HE-staining, the lipid droplets became smaller, and the number of mitochondria increased. The mitochondrial structure was remodeled under the electron microscope. The expression of UCP1, PGC-1α and PKA was elevated in iWAT detected by RT-qPCR (p < 0.05 or p < 0.001). In vitro, compared with the control group, 0.8 mg/mL DZF intervention significantly increased the number of mitochondria and expression of UCP1, PGC-1α, PKA, and pCREB (p < 0.05 or p < 0.01). In contrast, UCP1 and PGC-1α expression were significantly reversed after adding PKA inhibitor H-89 dihydrochloride. Conclusion: DZF can promote UCP1 expression by activating the PKA pathway, thereby promoting browning of WAT, attenuating obesity, and reducing obesity-related glucose and lipid metabolism abnormalities, indicating that DZF has the potential to be selected as an anti-obesity drug to benefit obese patients.